Development of a highly sensitive luciferase assay for intracellular evaluation of coronavirus Mpro activity - Dong, Bao; Chen, Yuehong; Wang, Xin; Li, Jing; Zhang, Sen; Kang, Xiaoping; Li, Yuchang; Li, Biao; Liao, Liangning; Zhang, Zhengwei; Xiong, Jiaqi; Shao, Lele; et al. (Frontiers in Microbiology, 2025)
COVID-19, caused by SARS-CoV-2 virus, has emerged as a global threat to human health. The main protease (Mpro) of SARS-CoV-2 is an excellent target for the development of antiviral drugs against COVID-19, and various protease biosensors have been developed to evaluate anti-coronavirus drugs. However, the application of these protease biosensors was limited due to high background fluorescence, poor signal-to-noise ratios, and constraints in enzyme activity thresholds for accessing live viruses. In this study, we rationally designed a highly conserved Mpro cleavage site sequence among different coronaviruses (CoVs) with high proteolytic activity, and described an intracellular coronavirus Mpro proteolytic (ICMP) reporter system that takes advantage of virus-encoded Mpro expressed in infected cells to reform the NanoBiT fluorescent protein. The system can be used to visualize and identify cells infected with coronavirus, and demonstrated high compatibility with various Mpro proteins from 13 different mammalian coronaviruses (covering α, β, γ, and δ CoVs), exhibiting at least a 1,030-fold increase in luminescence. Stronger Nluc signals were detectable with CoV 229E virus infection at a MOI of 0.001. Additionally, the system proved suitable for evaluating and screening of antiviral compounds, including lufotrelvir, GC376, Nirmatrelvir, X77, MG-101, and the potential inhibitor Cynaroside. The ICMP system is not only an invaluable tool for the detection of live coronaviruses, but also for the discovery of antivirals against current and future pandemic coronaviruses.